2012
DOI: 10.1021/ol302098u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of S-Linked Glycoconjugates and S-Disaccharides by Thiol–Ene Coupling Reaction of Enoses

Abstract: Free-radical hydrothiolation of the endocyclic double bond of enoses is reported. Reaction between 2-acetoxy-D-glucal and a range of thiols including amino acid, peptide, glycosyl thiols, and sugars with primary or secondary thiol functions gave S-linked α-glucoconjugates and S-disaccharides with full regio- and stereoselectivity. Addition of glycosyl thiols to a 2,3-unsaturated glycoside also proceeded with good selectivity and afforded a series of 3-deoxy-S-disaccharides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 44 publications
1
72
1
Order By: Relevance
“…17 Thus, the reactions were carried out in toluene at room temperature with a 2 : 1 thiol : ene ratio by irradiation at λ max 365 nm for 3 × 15 min in the presence of 2,2-dimethoxy-2-phenylacetophenone (DPAP) (3 × 0.1 equiv.) as the cleavable photoinitiator 1a (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…17 Thus, the reactions were carried out in toluene at room temperature with a 2 : 1 thiol : ene ratio by irradiation at λ max 365 nm for 3 × 15 min in the presence of 2,2-dimethoxy-2-phenylacetophenone (DPAP) (3 × 0.1 equiv.) as the cleavable photoinitiator 1a (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In those cases, significantly enhanced yields could be reached by changing the tolueneMeOH systems to DMF-water. 17 Here, we decided to study how the solvent affects the reaction when low conversion was observed in toluene. Thus, the reaction of 2-acetoxy glycal 1 and thiol 2c was carried out in different solvents with a thiolene ratio of 2 : 1, irradiating at λ max 365 nm for 3 × 15 min (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations